Pectin Red Dragon Fruit Peel Pectin-Based Microspheres for Oral Quercetin Delivery: Characterization, Stability Study, Digestion Resistance, and Cytotoxicity Against HeLa Cells - Kurniawan, Muhammad Fariez; Setyawan, Dwi; Hariyadi, Dewi Melani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
This study aims to evaluate the potential of red dragon fruit skin pectin to be used as a polymer compared with commercial pectin in the quercetin microsphere. Microspheres were made using the ionic gelation technique. Ten formulas were created, utilizing pectin from red dragon skin extracted with oxalic acid (OA75), citric acid (CA75), acetic acid (AA75), and commercial pectin at 1% and 1.5% concentrations. A gel permeation chromatography test (GPC) was performed to evaluate pectin’s molecule weight. Parameters were assessed, including yield, moisture content (MC), Carr’s Index, Hausner ratio, swelling index, Fourier Transform Infrared Spectroscopy (FTIR), particle size, polydispersity index (PDI), drug loading (DL), encapsulation efficiency (EE), Scanning Electron Microscope (SEM), in vitro drug release, accelerated stability test at a temperature of 40±2oC and RH 75±5% for 3 months and thermal stability test in the form of DSC and XRD at the same temperature and humidity for 9 months, digestion resistance with incubation in artificial stomach and intestinal solution for 4 hours continued with cytotoxicity test on HeLa cells with MTT Assays. Results of FTIR indicate a strong interaction between quercetin and pectin in forming a stable microsphere structure; SEM showed the spheres morphologically. The kinetics of quercetin release from microspheres was the Korsmeyer-Peppas model. DL and EE had no significant differences for 3 months and no significant changes in the glass transition in the DSC test during testing until month 9. The FF formulation (1.5% AA75) had the highest cytotoxic activity against HeLa cells and a high Selectivity Index.